Head Lice - Rebecca W. Baldwin; Faith M. Oi (EDIS)
Revised! ENY-296, a 6-page illustrated fact sheet by R. W. Baldwin and F. M. Oi, describes this pest of humans which infests 10-12 million people each year in the United States, its biology, prevention, treatment, and management, including best practices for inspection, removal, and treatment. Includes frequently asked questions, references and tables listing over-the-counter and prescription-only products for management of head lice. Published by the UF Department of Entomology and Nematology, June 2007.